#TITLE_ALTERNATIVE# - SEIZARWATI (NIM 12805009); Pembimbing : Dra. Atika Lubis, MS. dan Dr. Edvin Aldrian, B.Eng, M., WULAN
This research concerned on the effect of forest ratio change to some climate parameters, such as surface temperature, surface evaporation, and convective precipitation over Borneo Island. This simulation is uses regional climate model REMO, developed by Max Plank Institute. Input data is taken from ECMWF reanalysis data (ERA 15) during 15 years from 1979 until 1993. The parameters change is showed by an anomaly. Anomaly is the difference between parameters value on each scenarios with control simulation (baseline). In this case, vegetation ratio data from USGS was modified to obtain four different condition of forest cover. The first as control (baseline), forest ratio is not changed; the second, forest ratio decreased by 25%; the third, forest ratio decreased by 50%; and the fourth, forest ratio increased by 20%. Another surface parameter, such as: surface albedo, leaf area index, vegetation type, and field capacity of soil also changed. The way to change the forest ratio is by using random method at the initial condition. By using a program, vegetation ratio on each grid is changed automatically until the total ratio is appropriate with scenario and this changes are assumed to be static during 15 years. Simulation with four different condition of forest cover shows the change of surface climate parameters. Deforestation can affect surface temperature increase, surface evaporation decrease, and precipitation pattern and intensity are changed. Spatially, surface temperature anomaly between deforestation scenario 25%-control is 0.1-2.5 K, deforestation scenario 50%-control is 0.2-5 K, while reforestation scenario 20%-control is 0-(-2.5) K. Temporally, surface temperature shows anomaly trend from year to year. Surface evaporation spatially between deforestation 25%-control is 0-0.6 mm/day, deforestation scenario 50% - control is 0.2-0.9 mm/day, while reforestation scenario 20%-control is 0-(-0.4) mm/day. Spatially, convective precipitation change is not homogenous all over the region, intensity of precipitation increases in some region and decreases in another region.